Insight into the Molecular Characteristics of Langhans Giant Cell by Combination of Laser Capture Microdissection and RNA Sequencing - Chen Y; Jiang H; Xiong J; Shang J; Chen Z; Wu A; Wang H (Dove Medical Press, 2022)
Yanqing Chen,1 Haiqin Jiang,1 Jingshu Xiong,1 Jingzhe Shang,2,3 Zhiming Chen,1 Aiping Wu,2,3 Hongsheng Wang1 1Jiangsu Key Laboratory of Molecular Biology for Skin Diseases and STIs, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, Nanjing, People's Republic of China; 2Center for Systems Medicine, Institute of Basic Medical Sciences, Chinese Academy of Medical Sciences and Peking Union Medical College, Suzhou, People's Republic of China; 3Center of Systems Medicine, Suzhou Institute of Systems Medicine, Suzhou, People's Republic of ChinaCorrespondence: Hongsheng Wang; Haiqin JiangJiangsu Key Laboratory of Molecular Biology for Skin Diseases and STIs, Institute of Dermatology, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 12, St Jiangwangmiao, Nanjing, 210042, Jiangsu, People's Republic of China, Tel +86-25-85478953, Fax +86-25-85478944, Email whs33@vip.sina.com; hq_j1985@126.comPurpose: The presence of Langhans giant cell (LGC) is a hallmark of mycobacterium-induced granuloma. The molecular characteristics and functions of LGC remain unclear to date. The study aimed to systematically characterize the molecular characteristics of LGC and reveal the potential functions.Methods: Human LGCs were purified through laser capture microdissection (LCM) in vitro. RNA sequencing and in-depth transcriptome analysis were performed for purified LGCs and macrophages in the same system. Skin samples from mycobacterial infection patients were used to confirm some of the transcriptional expression.Results: Human LGCs have different expression pattern from macrophages in the same in vitro system. A total of 967 differentially expressed genes were found. Bioinformatics analysis showed that LGCs are is characterized by active cell shape regulation, increased cytoskeletal components, weakened energy metabolism level, and reduced immune response. CCL7 may be a specific molecular for LGC to communicate with CCR1-expression cells in granuloma.Conclusion: LGCs have unique molecular characteristics different from that of macrophages. They may play a role in maintaining the hemostasis in granuloma.Keywords: langhans giant cell, transcriptome analysis, laser capture microdissection, molecular characteristics, CCL7